Problem-Gambling Severity and Psychiatric Disorders among American-Indian/Alaska Native Adults - Kong, Grace (J Psychiatr Res, 2015)
INTRODUCTION: Little is known about the association between problem-gambling severity and psychiatric disorders among American-Indian/Alaska-Native (AI/AN) individuals. Thus, we examined these factors among a nationally representative sample of AI/AN and other American adults in the USA. METHOD: Using the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC) data, we conducted separate Wald tests and multinomial logistic regression analyses comparing AI/AN to black/African American, white/Caucasian, and all other racial/ethnic groups, respectively. RESULTS: Relative to other American adults, AI/AN adults were least likely to report non-/low-frequency gambling (NG: AI/AN 66.5%, white/Caucasian 70.5%, black/African American 72.8%, other racial/ethnic group 72.3%) and most likely to report low-risk gambling (LRG: AI/AN 30.1%, white/Caucasian 26.5%, black/African American 23.4%, other racial/ethnic group 24.7%). The association between at-risk/problem-gambling (ARPG) and any past-year Axis-I disorder was stronger among AI/AN versus other American adults. Although ARPG and LRG were associated with multiple past-year Axis-I and lifetime Axis-II psychiatric disorders in both AI/AN and other American adults, LRG was more strongly associated with both Axis-I disorders (particularly major depression, generalized anxiety disorder and nicotine dependence) and Cluster-B Axis-II (particularly antisocial personality disorder) disorders in AI/AN versus other American adults. DISCUSSION: A stronger association between problem-gambling severity and past-year psychiatric disorders among AI/AN relative to other American adults suggests the importance of enhancing mental health and problem-gambling prevention and treatment strategies that may help AI/AN individuals.